Analisis Rasio Likuiditas, Solvabilitas dan Rentabilitas pada Perseroan Terbatas (PT) Pradiksi Gunatama Tbk - Amir Hamzah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
Abstract. The aim of this research is to determine the level of development of liquidity, solvency and profitability ratios at PT. Prediction of Gunatama, Tbk in Batu Engau District by analyzing financial reports for the 2018, 2019 and 2020 periods using liquidity, solvency and profitability ratio analysis. Based on the results of Liquidity Ratio Analysis at PT. Gunatama, Tbk's prediction for the Current Ratio in 2018 is 3.4 times, in 2019 it is 1.1 times, and in 2020 it is 1.5 times. The Quick Ratio in 2018 was 3.2 times, in 2019 it was 0.7 times and in 2020 it was 1.2 times. The Cash Ratio in 2018 was 2%, in 2019 it was 4%, and in 2020 it was 18%. Based on the results of the Solvency Ratio Analysis at PT. Gunatama, Tbk's prediction for the Debt to Asset Ratio in 2018 is 60%, in 2019 it is 45%, and in 2020 it is 39%. Debt to Equity Ratio in 2018 was 148%, in 2019 it was 81% and for 2020 it was 64%. LTDtER in 2018 was 131%, in 2019 it was 67% and for 2020 it was 50%. Based on the results of Profitability Ratio Analysis at PT. Gunatama, Tbk's prediction for Profit Margin in 2018 is 6%, in 2019 it is 18% and for 2020 it is 26%. Net Profit Margin in 2018 was 21%, in 2019 it was 39% and for 2020 it was 17%. Return On Investment in 2018 was 39%, in 2019 it was 14% and for 2020 it was 71%. Return On Equity in 2018 was 96%, in 2019 it was 25% and for 2020 it was 12%.